Mangifera and Impatiens from Sumatra: Phylogenetic Positions and their Modes of Action as Anticancer Agents - Nurcahyanti, Agustina Dwi Retno (Pharmacognosy Reviews)
Cancer has become a growing health threat due to the emergence of multidrug resistance and the increasing diversity of cancer cells. The continuous investigation into the development of anticancer agents and treatments is crucial because the current treatments can cause adverse side effects and are often ineffective. Anticancer derived medicinal plants are a potential source of treatment. However, the abundance of medicinal plant species can cause several problems, like the adulteration. The author aims to demonstrate DNA Barcoding technique as a tool to perform phylogenetic positions of Mangifera and Impatiens species grown in Sumatra. The phylogenetic positions of the plants are supported by the review on the active secondary metabolites from Mangifera and Impatiens. The current study is based on unpublished work on DNA Barcoding technique, an established modern technique to identify the phylogenetic position and also adulteration in medicinal plants. The review on the active secondary metabolites including the mechanism of action as anticancer is based on pertinent papers that were retrieved using relevant keywords in PubMed and Science Direct. Work using DNA Barcoding technique confirmed that Mangifera and Impatiens from Sumatra are closely related to Momordica foetida and Impatiens balsamina from other areas, indicating that they may share the same anticancer traits with those species. The mechanism of action of Mangifera and Impatiens includes inhibition of the cell cycle, cytotoxicity activity, apoptosis and leading to cell death, and anti‑angiogenesis activity. Further research on both species is needed to identify their relevant chemical components to potentially develop anticancer drugs, either as a single compound or as a drug combination with minimal side effects and also to determine possible adverse reactions.
Keywords: Anticancer; Impatiens; Mangifera; phylogeny; Sumatra